Character Strength Analysis based on Student Courage in Aquatic Activities in Elementary School - Nur, Lutfi; Suryana, Dodi; Agustian, Eka; Solihati, Elis (Prodi PGSD Penjas FPOK UPI, 2021)
Courage should be stimulated since childhood, so it is necessary to introduce aquatic activities from an early age. The initial ability of a child courage in doing aquatic activities in the swimming pool needs to be examined to describe a child initial condition before doing activities in water games. The purpose of this study was to describe and analyze the character strength based on the courage of elementary school students in aquatic activities. Descriptive research method was used to describe the research results. The population of this study included 21 Grade 3 students of the Laboratory Elementary School of UPI Tasikmalaya. All 21 students aged 9-10 years (11 males and 10 females) became samples of this study, selected through a total sampling technique, to fill out a google form questionnaire. The results, obtained from the character strength analysis based on the student courage in aquatic activities, showed that all of 21 children had a high level of courage. It implies that the result of this study can be used as a material for the preparation of intervention program through aquatic activities to further develop character strengths in elementary schools.